Clinical Characteristics of COVID-19 Patients With Gastrointestinal Symptoms: An Analysis of Seven Patients in China - Ai, Jin-Wei; Zi, Hao; Wang, Yong; Huang, Qiao; Wang, Na; Li, Lu-Yao; Pei, Bin; Ji, Jianguang; Zeng, Xian-Tao (Frontiers in Medicine, 2020)
Objectives Patients with novel coronavirus disease 2019 (COVID-19) can present with gastrointestinal symptoms as their initial symptoms or as the main manifestations during disease progression, but the clinical characteristics of these patients are still unknown. Methods We identified COVID-19 patients who admitted to Xiangyang No.1 People’s Hospital and presented with gastrointestinal symptoms as their initial or main symptoms. Their medical records were reviewed by two independent clinical scientists. The epidemiological and clinical characteristics as well as the clinical outcomes were analyzed. Results Among 107 confirmed COVID-19 cases, 7 (6.5%) of them presented with gastrointestinal symptoms. 3 patients had gastrointestinal symptoms as the initial symptoms and chief complaints, and 4 patients as the main symptoms during disease progression. 6 patients had symptoms of diarrhea (3-16 days), 7 with anorexia (7-22 days), 6 with upper abdominal discomfort (1-7 days), and 4 with nausea (1-7 days), 1 with heartburn lasting 2 days, and 2 with vomiting symptoms (1 day). The chest CT scan showed typical COVID-19 imaging features, and associated with the progression of the disease. During treatment, 2 patients developed critical illness with multiple organ dysfunctions and one died due to organ failure. Discussion COVID-19 patients with gastrointestinal symptoms are relatively rare and might be misdiagnosed. The clinical features include watery stools, anorexia, and upper abdominal discomfort. These patients may have severe disease and be associated with a poor prognosis. The underlying mechanisms of SARS-CoV-2 related gastrointestinal symptoms need to clarify in future studies.